2013
DOI: 10.1038/ejcn.2013.241
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between socioeconomic status and anemia prevalence in adolescent girls based on the fourth and fifth Korea National Health and Nutrition Examination Surveys

Abstract: Higher SES leads to lower prevalence of anemia and IDA in Korean adolescent girls. This may be due to the fact that higher SES individuals consume more iron and vitamin C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
43
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 16 publications
10
43
1
3
Order By: Relevance
“…Generally, a higher family income was associated with a lower risk of anemia, ID, and VAD . Likewise, family income was positively associated with serum retinol, serum ferritin, and Hb status . Dietary intake of Ca and vitamin C was also reportedly higher with increasing household income level among South Korean adolescent girls .…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Generally, a higher family income was associated with a lower risk of anemia, ID, and VAD . Likewise, family income was positively associated with serum retinol, serum ferritin, and Hb status . Dietary intake of Ca and vitamin C was also reportedly higher with increasing household income level among South Korean adolescent girls .…”
Section: Resultsmentioning
confidence: 86%
“…46 Likewise, family income was positively associated with serum retinol, 121 serum ferritin, 124 and Hb status. 119,124 Dietary intake of Ca and vitamin C was also reportedly higher with increasing household income level among South Korean adolescent girls. 102 A unit increase in per capita expenditure on food was positively associated with a higher serum retinol among adolescent boys 114 and girls 121 in Bangladesh.…”
Section: Determinants Of Micronutrient Status and Deficienciesmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, IDA was more common in students and housewives, while ACD was in those who were on regular office work. These expected results were explained by increased prevalence of iron deficiency and chronic inflammatory diseases in females and higher vegans in rural communities [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In this study both AA and IDA were related to low socio-economic status, these findings confirmed the previously reported association of low socio-economic status with anemia. [17][18][19] Why AA is related to socio-economic status? This could be explained by the extensive exposure to environmental and infectious factors that could predispose to AA.…”
Section: Discussionmentioning
confidence: 99%